2020
DOI: 10.1002/berj.3662
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners' perspectives and experiences of supporting bilingual pupils on the autism spectrum in two linguistically different educational settings

Abstract: With greater linguistic diversity in educational settings around the world as a result of international migration, and a rise in autism diagnoses, educators are more frequently teaching children who are both neurodiverse and linguistically different to their peers. The aim of the present study was to uncover the perspectives and experiences of educational practitioners who provide support for bilingual learners on the autism spectrum in two linguistically different educational settings: England and Wales. Semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
1
25
1
Order By: Relevance
“…Based on previous research and suggested sample sizes for phenomenological studies (Guest, Bunce, & Johnson, 2013 ; Howard et al, 2019b , 2020a , b ; Morgan et al, 2002 ), we aimed to recruit 15 practitioners and 15 parents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous research and suggested sample sizes for phenomenological studies (Guest, Bunce, & Johnson, 2013 ; Howard et al, 2019b , 2020a , b ; Morgan et al, 2002 ), we aimed to recruit 15 practitioners and 15 parents.…”
Section: Methodsmentioning
confidence: 99%
“…Forced monolingualism may also impair communication between monolingual children and bilingual parents and family, which undermines the child’s ability to interact and build relationships with immediate and extended family (Beauchamp & MacLeod, 2017 ; Kremer-Sadlik, 2005 ; Yu, 2013 ). Furthermore, such recommendations are not sensitive to the aspirations of bilingual parents, who often desire that their autistic children attain bilingual ability (Howard, Gibson, & Katsos, 2020a ; Howard, Katsos, & Gibson, 2020b ; Kay-Raining Bird et al, 2012 ; Yu, 2013 ). The present research answers calls for further research on parental and practitioner perspectives on bilingualism among autistic children in specialist schools and in more diverse linguistic contexts (Howard, Katsos, & Gibson, 2019b , 2020a , b ; Howard, Katsos, & Gibson, 2020c ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In England, at least one in five pupils has English as an additional language, and this number is steadily rising (Leung, 2010 ; Department for Education, 2018 ). Despite this, a recent interview study with UK-based educators supporting autistic bilingual children (Howard et al, 2021 ) showed that although educators hold positive views about bilingualism, opinions vary greatly when it comes to autistic pupils. Many reported not recommending bilingualism for all autistic children, and this was predominantly based on the child's language abilities and autism profile.…”
Section: Educationmentioning
confidence: 99%
“…Monolingual educators, particularly those in monolingual environments, may underestimate the link between bilingualism, identity and inclusion, and a greater linguistic and cultural diversity amongst educators could help them better understand the experiences and needs of their autistic bilingual pupils (Yu and Hsia, 2019 ). Additionally, including dedicated training would help address some of the misconceptions expressed by educators (Iadarola et al, 2015 ; Howard et al, 2021 ) who often have limited experience with autistic bilingual pupils.…”
Section: Educationmentioning
confidence: 99%